Molecular studies on HSV: replication rate, infection capacity and progeny - Azevedo, Aleksandra Inês Mazurek Vieira de (2017)
Herpes simplex viruses (HSV) are ubiquitous host-adapted pathogens that cause a variety of different disorders. There are two sub-types: HSV-1, which is traditionally associated with oro-facial infections, and HSV-2 that is mostly associated with genital ulcers. This distinction, however, is becoming less evident since HSV-1 frequency in genital infections is increasing due to social, demographic and migratory tendencies, making genital herpes one of the most prevalent sexually transmitted infections worldwide. A better understanding on genital HSV-1 and HSV-2 infections is mandatory to the pathogenesis of human herpes disease. The scope of this thesis was to evaluate the life cycle of various HSV-1 and HSV-2 genital clinical isolates with different viral loads in three distinct host cell lines, giving special focus on both capacity and efficiency of viral infection, in terms of replication rate and progeny. Our results showed that: i) both HSV-1 and HSV-2 isolates exhibited similar infection patterns regardless MOI, with DNA starting to be synthesized nearly at 6-12h post-infection; ii) regardless HSV subtype, initial viral concentrations do not apparently affect adherence to any host cell line nor the generated progeny; iii) Vero E6 cells seemed the most appropriated cell line for HSV-2 infection; iv) HeLa229 cells appeared to be the most suitable for HSV-1 infection for smaller inoculums; and v) Vero cell line had the worst viral growth results for both HSV subtypes. In general, HSV-2 displayed always lower both attachment capacities and growth rates than HSV-1, although higher progenies were seen in Vero E6 cell line. Overall, the findings presented in this MSc thesis will certainly constitute a step forward for the understanding of the pathogenesis of the human herpes genital infections.